Det kgl. Landhusholdningsselskabs Generalforsamling den 14de December 1876. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling den 14de December 1876.